Improving The Speaking Ability Of Students In Class IV.a SD Negeri 0411 Ujung Batu Through Vocabulary Card Media - Helmida Hasibuan; Rinja Efendi (Indonesian Journal of Basic Education, 2021)
The purpose of this study is (1) to find out how to improve speaking skills using vocabulary card media in fourth grade students of SD Negeri 0411 Ujung Batu in the academic year 2020/2021; (2) to determine the form of planning and implementation of learning to speak using vocabulary card media: (3) to find out the obstacles and results obtained from learning to speak using vocabulary card media, consisting of 20 students. This study also uses 2 (two) cycles starting from February to May 2021. From the results of the learning activities, it can be concluded as follows: (1) learning using vocabulary card media has a positive impact on improving speaking skills marked by an increase in students' speaking in each cycle, namely the first cycle obtained an average of 66.25 and in the second cycle obtained an average of 80; (2) the application of vocabulary card media in speaking skills has a positive influence, namely students are able to express and express ideas, and the results of students' scores meet the minimum completeness criteria